Optimalisasi Pengelolaan Klaim KUR Menggunakan Askrindo Core System pada PT Askrindo Surabaya - Farahdillah, Nadia Amara Dwi; Fitriani, Nurul (Forum Kerjasama Pendidikan Tinggi, 2025)
Efficiency in claims management is a crucial aspect for insurance companies to maintain profitability and operational sustainability. PT Askrindo, a state-owned enterprise in the field of credit insurance, has implemented the Askrindo Core System (ACS) as an integrated information system to enhance the effectiveness of the claims process for the People’s Business Credit (KUR) program. This study aims to analyze the extent to which the optimization of ACS can improve the company's financial efficiency, as well as to identify the challenges and strategies involved in its implementation. Using a qualitative approach, data were obtained through observation and interviews with finance staff at PT Askrindo Surabaya Branch. The results show that ACS is capable of accelerating the claims submission and disbursement processes, improving data accuracy, and reducing operational costs by up to 60%. However, there are technical obstacles such as system disruptions, as well as non-technical challenges including a lack of user understanding of the system. Continuous training and technical assistance are key to the successful implementation of ACS. The optimization of ACS has made a positive contribution to PT Askrindo's financial efficiency and can serve as a reference for other insurance companies in managing claims through digital systems.